An extremely highly selective flexible compliant tactile touch sensor sheet. Issue 9 (29th March 2016) - Nakata, Shogo; Kanao, Kenichiro; Harada, Shingo; Arie, Takayuki; Akita, Seiji; Takei, Kuniharu
Abstract : One of the major challenges toward widespread application of flexible tactile pressure sensors lies in the distinction between tactile pressure stimuli and contributions from substrate bending. To this point, this issue has been a bottleneck in further advancement of this class of devices. To address this issue, we demonstrate a flexible tactile pressure sensor sheet with extremely high selectivity between tactile pressure and substrate bending: these devices are designed with strain engineering with the goal of incorporation into artificial skin applications. In addition to characterizing the mechanical and electrical performance of the sensor, a first proof of concept for tactile pressure mapping at several mechanical flex states is conducted, demonstrating that these devices are highly compliant tactile pressure sensors well‐suited to robotic skin and prosthesis applications.